Active control of laminated composite plates using elliptical smart constrained layer damping treatment. (1st March 2019) - Sahoo, S.R.; Ray, M.C.
Abstract: In this article, performance of the elliptical patches of smart constrained layer damping (SCLD) treatment is investigated for controlling vibrations of smart laminated composite plates. A three dimensional mesh free model (MFM) has been implemented for the first time based on the element free Galerkin (EFG) method and layer wise displacement theory for studying the dynamic behavior of the composite plates integrated with the SCLD treatments. Symmetric/antisymmetric cross-ply and general angle-ply laminates are considered for the substrate of the smart composite plates. Circular and regular rectangular type patches are also considered for the analysis. It is observed that the elliptical SCLD patches are more efficient in attenuating the amplitude of vibration in the laminated composite plates as compared to the circular and square type patches. The results from numerical analysis also reveal that the elliptical patches have the maximum performance index followed by the circular and the square type SCLD patches in enhancing the active damping characteristics of smart composite plates. The performance of the elliptical patch is sensitive to the piezoelectric fiber orientation angle and becomes maximum if the piezoelectric fiber orientation is vertical irrespective of the types of SCLD patches considered as well as the lamination sequence.